1998
DOI: 10.1083/jcb.142.6.1559
|View full text |Cite
|
Sign up to set email alerts
|

The Xenopus Chk1 Protein Kinase Mediates a Caffeine-sensitive Pathway of Checkpoint Control in Cell-free Extracts

Abstract: We have analyzed the role of the protein kinase Chk1 in checkpoint control by using cell-free extracts from Xenopus eggs. Recombinant Xenopus Chk1 (Xchk1) phosphorylates the mitotic inducer Cdc25 in vitro on multiple sites including Ser-287. The Xchk1-catalyzed phosphorylation of Cdc25 on Ser-287 is sufficient to confer the binding of 14-3-3 proteins. Egg extracts from which Xchk1 has been removed by immunodepletion are strongly but not totally compromised in their ability to undergo a cell cycle delay in resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
264
1
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(286 citation statements)
references
References 52 publications
20
264
1
1
Order By: Relevance
“…Furthermore, caffeine, an agent capable of antagonizing As 2 O 3 -induced G 2 /M arrest, also blocked As 2 O 3 -induced Dj m collapse and apoptosis. Based on these observations as well as those reported by others, 21,22 we propose that mitotic arrest is a common mechanism for As 2 O 3 -induced apoptosis in most cancer cells. …”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Furthermore, caffeine, an agent capable of antagonizing As 2 O 3 -induced G 2 /M arrest, also blocked As 2 O 3 -induced Dj m collapse and apoptosis. Based on these observations as well as those reported by others, 21,22 we propose that mitotic arrest is a common mechanism for As 2 O 3 -induced apoptosis in most cancer cells. …”
Section: Discussionmentioning
confidence: 85%
“…Although caffeine has multiple effects on cell physiology, it was widely used to specifically relieve cells from early mitotic arrest. 22 Cyclin B1 and hCDC20 were upregulated while Tyr15 phosphorylation of p34 cdc2 was decreased upon treatment with 1.0 mM As 2 O 3…”
Section: Dtt Inhibited As 2 O 3 -Induced Mitotic Arrest In Nb4 Cellsmentioning
confidence: 99%
“…How ca eine is able to disrupt these checkpoint pathways is not yet fully understood but recent observations on Xenopus eggs suggest that ca eine could abolish the phosphorylation of Chk1, thus preventing the phosphorylation of Cdc25C on Ser-287 residue. The lack of phosphorylation of Cdc25C prevents its sequestration by 14 ± 3 ± 3 proteins, thus allowing the activation of CDK1 (Kumagai et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Studies with Xenopus egg extracts have demonstrated that the Chk1 pathway inhibits entry into mitosis in the presence of unreplicated or UVirradiated DNA (Kumagai et al, 1998a). The simplest explanation of the phenotype is that geminin deficiency causes a subtle defect in DNA structure that activates the pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Chk1 prevents Cdc2 dephosphorylation by negatively regulating Cdc25C, the phosphatase that removes the inhibitory phosphates from Cdc2. Chk1 phosphorylates Cdc25C on serine-287 (S287), generating a binding site for a member of the 14-3-3 family of proteins (Peng et al, 1997;Kumagai et al, 1998a;Kumagai and Dunphy, 1999). 14-3-3 binding masks a nuclear localization signal on Cdc25C and causes the phosphatase to be retained in the cytoplasm, where it presumably cannot dephosphorylate nuclear Cdc2.…”
Section: Bypassing Chk1 Pathway Suppresses G2 Arrest Caused By Geminimentioning
confidence: 99%